1998
DOI: 10.1128/jvi.72.4.3076-3081.1998
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies Protect against Lethal Flavivirus Challenge but Allow for the Development of Active Humoral Immunity to a Nonstructural Virus Protein

Abstract: Antibody-mediated neutralization of viruses has been extensively studied in vitro, but the precise mechanisms that account for antibody-mediated protection against viral infection in vivo still remain largely uncharacterized. The two points under discussion are antibodies conferring sterilizing immunity by neutralizing the virus inoculum or protection against the development of disease without complete inhibition of virus replication. For tick-borne encephalitis virus (TBEV), a flavivirus, transfer of neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…In addition, at least one other neutralizing epitope has been identified by a monoclonal antibody in the envelope glycoprotein 4 (Yang et al, 2000) and another one in the M envelope protein coded for by ORF6 (Yang et al, 2000). We should also bear in mind the recent reports demonstrating that antibodies against viral nonstructural proteins such as the cell-secreted glycoprotein NS1 of tickborne encephalitis (Kreil et al, 1998) and the NSP4 of rotavirus (Estes et al, 2001) have great significance for in vivo protective immunity. In the case of PRRSV, one nonstructural glycoprotein in certain strains of PRRSV, the glycoprotein 3, which seems to be secreted from virusinfected cells, has been reported to be protective but not an inducer of neutralizing antibodies (Plana-Duran et al, 1997b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, at least one other neutralizing epitope has been identified by a monoclonal antibody in the envelope glycoprotein 4 (Yang et al, 2000) and another one in the M envelope protein coded for by ORF6 (Yang et al, 2000). We should also bear in mind the recent reports demonstrating that antibodies against viral nonstructural proteins such as the cell-secreted glycoprotein NS1 of tickborne encephalitis (Kreil et al, 1998) and the NSP4 of rotavirus (Estes et al, 2001) have great significance for in vivo protective immunity. In the case of PRRSV, one nonstructural glycoprotein in certain strains of PRRSV, the glycoprotein 3, which seems to be secreted from virusinfected cells, has been reported to be protective but not an inducer of neutralizing antibodies (Plana-Duran et al, 1997b).…”
Section: Discussionmentioning
confidence: 98%
“…We know, from other viral systems, that protective antibodies may function not only by virus neutralization, but also by other mechanisms such as antibody-dependent cell-mediated cytotoxicity, or complement-dependent antibody-mediated cell lysis (Lindsay and Oldstone, 1996). Interestingly, it has been demonstrated that nonneutralizing antibodies directed against the nonstructural glycoprotein NS1 of the flavivirus tick-borne encephalitis virus (TBEV) can mediate and passively transfer protective immunity (Kreil et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Certain strains of mice have also been shown to be genetically resistant to flaviviruses. 21,22 Studies to define the ability of polyclonal or monoclonal antibodies (MAbs) to protect mice from virus challenge have been performed with JE, 23,24 Murray Valley encephalitis (MVE), 25,26 SLE, 27 and TBE [28][29][30][31][32][33][34][35][36] viruses. All of these studies have used MAbs specific for the envelope (E) glycoprotein, which is the major flaviviral antigen.…”
Section: Murine Models Of Flaviviral Encephalitis and Their Use In Evmentioning
confidence: 99%
“…CoP = Correlate of protection. www.nature.com/scientificreports www.nature.com/scientificreports/ to correlate with protection [23][24][25] . Further supporting this correlate of protection, it has been reported that passive transfer of Zika neutralizing monoclonal antibodies or antisera from vaccinated humans and animals to mice is sufficient to protect against ZIKV challenge 16,17,21,26 .…”
Section: Discussionmentioning
confidence: 99%